Analisis Docking Molekuler Senyawa Fitokimia Indonesia terhadap Protein Rhinovirus 2R06 - Kinanti Ratu Saylendra; Deski Beri (Lembaga Yasin AlSys, 2026)
Human Rhinovirus 14 (HRV14) is one of the main causes of upper respiratory tract infections and to date has no specific antiviral therapy. This study aims to analyze the potential of phytochemical compounds from Indonesian traditional plants against the VP1 protein of Rhinovirus 2R06 using an in silico molecular docking method. This study used a quantitative in silico-based approach with MOE 2022 software to evaluate the binding affinity and stability of ligand interactions with the viral receptor. The results showed that tannin, cowanol, and andrographolide had the best binding affinities, with S-scores of -11.6692, -10.2501, and -7.8695 kcal/mol, respectively. Low RMSD values indicated good stability of the ligand-receptor complexes, while the interactions formed were dominated by hydrogen bonds and electrostatic interactions with several important amino acid residues in the VP1 protein. Thus, phytochemical compounds from Indonesian traditional plants have the potential to be developed as natural antiviral candidates against Rhinovirus infection. This study provides an initial scientific basis for the development of plant-based therapeutic candidates, although further experimental validation is still required to confirm their effectiveness and biological mechanisms.